2006
DOI: 10.1542/peds.2006-0210
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residency Duty Hours Before and After Limitations

Abstract: Since the Accreditation Council for Graduate Medical Education duty hour limits went into effect, pediatric residents report working fewer hours and making fewer patient care errors because of fatigue. Although room for additional improvement remains, the experiences of residents and program directors suggest that implementation of the Accreditation Council for Graduate Medical Education limits in pediatric residency programs is improving resident well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Numerous studies have linked resident workload to wellness and education [1][2][3][4][5][6] ; however, the vast majority of existing research on resident workloads has focused on the quantity of hours worked, rather than the content of those hours. Additionally, most research has studied self-reported hours data, which can be unreliable.…”
mentioning
confidence: 99%
“…Numerous studies have linked resident workload to wellness and education [1][2][3][4][5][6] ; however, the vast majority of existing research on resident workloads has focused on the quantity of hours worked, rather than the content of those hours. Additionally, most research has studied self-reported hours data, which can be unreliable.…”
mentioning
confidence: 99%
“…Next, we selected substitute providers. After 2003, programs shifted work among existing residents, hired midlevel providers (nurse practitioners and physician assistants), and gave attendings additional responsibilities; teaching hospitals hired more nurses 10,[17][18][19][20][21][22][23][24][25] . Few programs expanded, likely because the Balanced Budget Act caps Medicare-supported residency positions 26 .…”
Section: Individual Requirementsmentioning
confidence: 99%
“…After implementation of the 2003 duty hour limitations, fully 73% of residents in that survey still reported falling asleep during a conference, 20% reported falling asleep while driving from work, 8% reported making an error in patient care because of fatigue, and 14% to 18% reported working more than 80 h/wk on inpatient and critical care services. 23 Consecutive duty hours of 16 hours or less are associated with marked decreases in attention failures and serious medical errors. 24 National and international legal initiatives to hold administrators responsible for medical errors and even MVAs caused by fatigued residents 25 provide additional imperatives for elimination of 24-hour call from all residency programs in the United States.…”
Section: Discussionmentioning
confidence: 99%